(E)-1-Methyl-4-[2-(2-naphthyl)vinyl]pyridinium iodide - Fun, Hoong-Kun (International Union of Crystallography, 2009)

(untitled)
In the title compound, C(18)H(16)N(+)·I(−), the cation is disordered over two orientations related by a 180° rotation about its long axis with occupancies of 0.554 (7) and 0.446 (7). Both disorder components exist in an E configuration. The dihedral angle between the pyridinium ring and the naphthalene ring system is 4.7 (6)° in the major disorder component and 1.6 (8)° in the minor component. In the crystal structure, centrosymmetrically related cations are stacked along the a axis, with significant π–π interactions between the pyridinium ring and the naphthalene ring system [centroid-centroid distance = 3.442 (9) Å]. The iodide ions are located between adjacent columns of cations. The cations are linked to the iodide ions by C—H⋯I interactions. Weak C—H⋯π interactions involving the methyl group are also observed.